Chemical resistance of plastics and elastomers - Plastics Design Library (Norwich, N.Y. Plastics Design Library, 2008)
A compilation of data that explains the effect of thousands of reagents, the environment and other exposure media on the properties and characteristics of plastics and elastomers.
Analiza P. Rollon
Text
Hardware Requirements: Pentium 2/Celeron or higher; 500 MB free space; 256 MB RAM
System Requirements: Windows 98/XP
Keywords: Plastics -- Chemical resistance; Elastomers -- Chemical resistance